The other parent : the inside story of the media's effect on our children - Steyer, James P. (New York : Atria Books, 2003)
Examines how we have allowed media to bombard our children's lives and offers practical advice on countering the incessant parade of images that frighten, intrigue, and influence America's kids.
At home with the other parent -- It's all about the money -- Sex sells -- Meida violence : in harm's way -- The selling of kids as consumers -- The politics of media and kids -- The power of campaign cash -- It all starts at home -- Calling the media industry to account -- Protecting the public interest -- The challenge of citizen action.
"First Atria Books trade paperback printing May 2003."
Includes bibliographical references (p. [257]-268) and index.
Keywords: Mass media and children -- United States; Violence in mass media; Parenting; Mass media -- United States -- Public opinion; Public opinion -- United States